Analysis of Tax Report Compliance on Salary Receipts and Incentives for Private Teachers on Ownership of NPWP: Analisis Kepatuhan Pelaporan Pajak Atas Penerimaan Gaji dan Insentif Guru Swasta Terhadap Kepemilikan NPWP - Anggraini Normaria Rahayu; Fityan Izza Noor Abidin (Academia Open, 2022)
Analysis of Tax Report Compliance on Salary Receipts and Incentives for Private Teachers on Ownership of Npwp, this thesis is not published. Faculty of Business, Law and Social Sciences, University of Muhammadiyah Sidoarjo. This study aims to determine the compliance of tax reporting on salary receipts and incentives for private school teachers to the ownership of a Taxpayer Identification Number (NPWP). This study uses a qualitative method. Data collection techniques by means of interviews, observation, and documentation. The data validity test used the triangulation test. The data analysis technique uses the stages of data collection, data reduction, data presentation, and drawing conclusions. The data collection technique used unstructured interviews with 4 teachers of Krian 1 Sidoarjo Vocational High School.The results of this study indicate that compliance with tax reporting on salary and incentive receipts in Krian 1 Sidoarjo Vocational High School teachers on average tax reporting compliance is at the category level, namely 25% low. In this study, the teacher has a NPWP as an administrative requirement and does not perform its obligation to report. Highlights: This study focuses on examining tax report compliance regarding salary receipts and incentives among private school teachers, specifically in Krian 1 Sidoarjo Vocational High School. The qualitative method was used, and data was collected through interviews, observation, and documentation, with data validity tested through triangulation. The findings indicate that there is a low level of tax reporting compliance among the teachers, despite having a Taxpayer Identification Number (NPWP) as an administrative requirement. Keywords: tax report compliance, salary receipts, incentives, private school teachers, NPWP.